PENINGKATAN HASIL BELAJAR BAHASA INGGRIS MATERI EXPLORING FAUNA OF INDONESIA MELALUI MODEL PROBLEM BASED LEARNING DI UPT SMP NEGERI 4 TAKALAR - Andi Nugraha Sirajuddin; Muh Rafi Samudra (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
This study aims to improve the learning outcomes of Class IX A students at UPT SMP Negeri 4 Takalar in English, specifically on the topic of Exploring Fauna of Indonesia, through the implementation of the Problem-Based Learning (PBL) model. The method employed is Classroom Action Research (CAR) based on the Kemmis and McTaggart spiral model, conducted in two cycles comprising planning, acting, observing, and reflecting stages. The research subjects consisted of 29 students, including 15 males and 14 females. Data collection instruments included essay-type learning outcome tests to measure the cognitive domain, as well as observation sheets to assess the affective and psychomotor domains. The results indicated a gradual improvement in student learning outcomes. In Cycle I, the class average reached 77.69 with a classical completeness percentage of 41.38%. This achievement increased in Cycle II, with the class average rising to 78.76 and the classical completeness percentage reaching 55.17%. Beyond academic improvement, the implementation of the PBL model proved effective in enhancing student activity, independence, and courage in presenting discussion results on fauna report texts.